2006
DOI: 10.1592/phco.26.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage: An Overview of Pharmacologic Management

Abstract: Cerebral vasospasm remains one of the leading causes of mortality in patients who experience a subarachnoid hemorrhage but survive the initial 24 hours. Vasospasm generally occurs 3-4 days after the initial subarachnoid hemorrhage and peaks at 5-7 days. The pathophysiology of vasospasm is poorly understood, which directly contributes to the inconsistency of management and creates a formidable challenge in clinical practice. Traditionally, hemodilution, hypervolemia, and induced hypertension (so-called triple H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 119 publications
(164 reference statements)
1
18
0
4
Order By: Relevance
“…Significant hypotension was reported in 34.5% of the nicardipine group as compared to 17.5% for the control group [19]. Many have suggested that the adverse effects of hypotension may have negated any beneficial effects on outcome [16,17,21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Significant hypotension was reported in 34.5% of the nicardipine group as compared to 17.5% for the control group [19]. Many have suggested that the adverse effects of hypotension may have negated any beneficial effects on outcome [16,17,21].…”
Section: Discussionmentioning
confidence: 98%
“…This reduces the activity of endogenous vasodilators such as nitric oxide and prostacyclines as well as increases the activity of endogenous vasoconstrictors (i.e., endothelins). The net effect is an increase in calcium dependent vascular smooth muscle contraction and luminal narrowing of the cerebral vessels [16][17][18]. Dihydropyridine calcium channel blockers including nimodipine and nicardipine primarily affect L-type slow conducting calcium channels on vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Menos experiencia existe con la monitorización de la presión tisular de oxígeno cerebral, la microdiálisis cerebral o la electroencefalografía como monitores de isquemia cerebral por VE, pero son pruebas potencialmente útiles 47,56 . Para la prevención de esta temible complicación se han estudiado múltiples opciones terapéuticas con resultados desiguales [57][58][59] . Los antagonistas del calcio mejoran los resultados en pacientes con HSA aneurismática, con una RRR de resultado desfavorable (definida como muerte, estado vegetativo o discapacidad grave) del 18% y una RAR del 5,1% 44 .…”
Section: Prevención Y Tratamiento De La Isquemia Cerebral Diferidaunclassified
“…La expansión del volumen circulatorio para prevenir la isquemia cerebral diferida no encuentra soporte firme 40 ni tampoco la triple H (hipertensión, hipervolemia y hemodilución inducidas) 67,68 . Otros fármacos o medidas como fibrinolíticos intracisternales, tirilazad, ciclosporina, eritropoyetina, nitroprusiato, estatinas, antagonistas selectivos de los receptores de la endotelina A, inhibidores de la fosfodiesterasa y otros (tabla 5) no han demostrado beneficio neto en ensayos clínicos adecuadamente controlados y de suficiente potencia [58][59] . El diagnóstico de isquemia cerebral diferida con frecuencia se define mal o no se define en absoluto en los estudios.…”
Section: Prevención Y Tratamiento De La Isquemia Cerebral Diferidaunclassified
“…Evidence for an important role for ET-1 in cerebral microcirculation is based on the demonstration that ET-1 antagonists and agents that interfere with its biosynthesis ameliorated the consequences of SAH-induced cerebral microvascular dysfunction (Yakubu and Leffler, 1996;Sobey and Faraci, 1998). Despite this important observation, therapeutic strategies to treat brain trauma-induced cerebral deficit are still lacking (Liu-Deryke and Rhoney, 2006;MacDonald, 2006).…”
mentioning
confidence: 99%